2015
DOI: 10.1002/ptr.5399
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation on the Antimicrobial Activity of Listerine®, Its Components, and of Mixtures Thereof

Abstract: Listerine® is one of the most popular mouthwashes worldwide and claims to combat harmful bacteria. In the past century, its recipe was changed from an essential oil mouthwash to a five-component mixture (thymol, menthol, eucalyptol, and methyl salicylate dissolved in 27% ethanol). The aim of this study was to get preliminary information about the antimicrobial activities of individual Listerine® components and their mixtures. We tested the bacterial strains Streptococcus mutans, Enterococcus faecalis, and Eike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 29 publications
2
33
1
2
Order By: Relevance
“…Interestingly, only one of the 16 clinical studies used a 22% ethanol solution as a control (Cosyn et al, 2013). Because ethanol in high concentrations contributes to the antibacterial effect (Vlachojannis et al, 2015), testing against a 5% ethanol solution (as a negative control) might be worthwhile.…”
Section: Efficacy Of Listerine®mentioning
confidence: 99%
“…Interestingly, only one of the 16 clinical studies used a 22% ethanol solution as a control (Cosyn et al, 2013). Because ethanol in high concentrations contributes to the antibacterial effect (Vlachojannis et al, 2015), testing against a 5% ethanol solution (as a negative control) might be worthwhile.…”
Section: Efficacy Of Listerine®mentioning
confidence: 99%
“…It also demonstrated that it affects cell membrane damage and hence the release of intracellular substances and changes in transmembrane potential (Shapiro and Guggenheim, 1995), probably not acting on calcium TRP channel receptors but through mitochondrial damage and stimulation on apoptosis. Then there is 3.94mM methyl salicylate for which a pilot document for the determination of the initial in vitro dose for acute toxicity testing has been found to have an LC50 value of 1.7mM (Website, 2001;Vlachojannis, 2015). Eucalyptol in Listerine has the least toxic effect (Ribeiro et al, 2006;Wang et al, 2012), but it has also been shown by SEM microscopy it can cause damage the cells (Dörsam et al, 2014;Zengin & Baysal, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, limited evidence on the efficacy of EO À E is available (Antunes et al, 2015;Vlachojannis et al, 2016. In Listerine Zero® (Vlachojannis et al, 2015) and Listerine® Natural Care, the EO (phenolic compounds) are dissolved by means of a patented mechanism using sodium lauryl sulfate (SLS). In the present study, it was not possible to test the effect of the EO À E on the epithelial cell migration using our model, because cells adjacent to the wound margin were easily detached from the culture plate upon contact with a pipette tip.…”
Section: Essential Oil Mouthrinse and Gingival Epithelial Cellsmentioning
confidence: 99%